PENGELOLAAN EMISI GAS LANDFILL (BIOGAS) SEBAGAI ENERGI TERBARUKAN - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2017)
The final landfill is a place to hoard the garbage and the bin gets the last treatment. The final disposal site may be either deep or field-shaped. In recent years, dumped end landfills have finally been converted to a public open space. Final waste disposal site is one of the biggest sources of landfill gas emissions in Indonesia. In the anaerobic process, the organic material decomposes and the landfill gas is produced. This gas then converges and rises regardless of the atmosphere. This becomes dangerous because it can cause an explosion, but it can also cause photochemical smog.